1983
DOI: 10.1128/aac.23.3.458
|View full text |Cite
|
Sign up to set email alerts
|

Differences in side effects of amantadine hydrochloride and rimantadine hydrochloride relate to differences in pharmacokinetics

Abstract: In a double-blind, placebo-controlied study, the comparative toxicities and blood concentrations of amantadine hydrochloride and rimantadine hydrochloride were determined. Healthy, working adults ingested either 200 (n = 52) or 300 mg (n = 1%) per day in divided doses for 4.5 days. Mean plasma drug concentrations at 4 h after the first dose were lower in rimantadine recipients given 100-(140 versus 300 ng/ml for rimantadine and amantadine, respectively; P < 10-5) or 200-mg doses (310 versus 633 ng/ml; P < 10-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 33 publications
(28 reference statements)
0
63
0
Order By: Relevance
“…Rimantadine is an analog of amantadine, differing only in the replacement of the amino group at position one with a methyl amine group; rimantadine pretreatment significantly inhibited PAF priming of the fMLP-activated respiratory burst at concentrations 10-fold lower (70). The C max of rimantadine is 74 ng/ml (0.3 M) 6 h after an initial dose of 100 mg, indicating that physiologic concentrations are close to the in vitro concentrations required to inhibit PAF-mediated changes in PMN physiology (25,43). Thus, rimantadine may provide a better means to curtail the effect of PMN-mediated organ injury, e.g., the acute respiratory distress syndrome and postinjury organ failure, yet its effects on other clathrin-dependent and -independent endocytotic mechanisms in different tissues need to be more clearly defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rimantadine is an analog of amantadine, differing only in the replacement of the amino group at position one with a methyl amine group; rimantadine pretreatment significantly inhibited PAF priming of the fMLP-activated respiratory burst at concentrations 10-fold lower (70). The C max of rimantadine is 74 ng/ml (0.3 M) 6 h after an initial dose of 100 mg, indicating that physiologic concentrations are close to the in vitro concentrations required to inhibit PAF-mediated changes in PMN physiology (25,43). Thus, rimantadine may provide a better means to curtail the effect of PMN-mediated organ injury, e.g., the acute respiratory distress syndrome and postinjury organ failure, yet its effects on other clathrin-dependent and -independent endocytotic mechanisms in different tissues need to be more clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rimantadine appears to be a more physiological inhibitor than amantadine because of its ability to inhibit PAF priming at clinically relevant concentrations (25,43), and may represent an effective pharmacological approach to reduce PMN-mediated tissue damage in the injured or critically ill patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited in vitro and animal model results suggest that rimantadine has greater influenza A virusinhibitory activity than amantadine (7,15,19). More importantly, clinical studies have found that at equivalent oral dosages of 200 mg (5) or 300 mg (8) per day rimantadine is associated with significantly fewer central nervous system side effects than amantadine. The differences in side effect rates observed between the two drugs appear to be related to differences in plasma concentrations (8).…”
mentioning
confidence: 99%
“…In a more recent study, PD patients who switched to placebo after amantadine IR treatment for a mean of 3.4 years showed significant worsening of dyskinesia at a median of 7 days, suggesting that some patients derived benefit over this duration [10]. Although most patients with PD can tolerate amantadine IR doses of 81-161 mg daily (equivalent to 100-200 mg daily of amantadine hydrochloride [HCl]) (electronic supplementary Table 1), higher doses that may provide greater antidyskinetic benefit are associated with increased frequency of central nervous system (CNS) adverse events (AEs) [7,11]. Therefore, amantadine IR is typically administered in divided doses, even though its relatively long half-life (* 17 h) might support once-daily dosing [12].…”
Section: Introductionmentioning
confidence: 99%